Intellectual freedom manual - American Library Association. Office for Intellectual Freedom; IG Publishing (Chicago American Library Association, 2010)
Includes the most up-to-date intellectual freedom guidelines, policies, and interpretations of the Library Bill of Rights, including: newly amended and updated policies; a new chapter, "Interactivity and the Internet"; and other fresh material on intellectual freedom and privacy in online social networks.
PART I : Intellectual freedom and libraries : an overview. Intellectual freedom : an enduring and all-embracing concept / Candace D. Morgan -- ALA and intellectual freedom : a historical overview / Judith F. Krug and Candace D. Morgan -- Challenges and issues today / Candace D. Morgan -- -- PART II : Library Bill of Rights. Library Bill of Rights : policy statement -- Library Bill of Rights : interpretations -- -- PART III : Protecting the freedom to read. The freedom to read -- Libraries : an American value -- Policies and statements related to access to information, library resources, and library services -- Policies and statements related to confidentiality, privacy, and governmental intimidation -- -- PART IV : Code of ethics of the American Library Association. Code of ethics of the American Library Association -- Enforcement of the "Code of Ethics of the American Library Association" : questions and answers -- Resolutions on workplace speech -- Questions and answers on speech in the workplace : an explanatory statement of the "ALA Code of Ethics" -- -- PART V : Intellectual freedom and the law. Public libraries and the public forum doctrine / Theresa Chmara -- Minors' First Amendment rights to access information / Theresa Chmara -- Privacy and confidentiality in libraries / Deborah Caldwell-Stone -- -- PART VI : Preserving, protecting, and working for intellectual freedom. Preparing for and responding to challenges / Beverley Becker -- Communicating the intellectual freedom message / Larra Clark with Macey Morales -- Lobbying for intellectual freedom / ALA Washington Office -- Rallying for intellectual freedom : where to go for help and how you can help / Angela Maycock and Nanette Perez.
Electronic reproduction.
Keywords: Libraries -- Censorship -- United States -- Handbooks, manuals, etc; Intellectual freedom -- United States -- Handbooks, manuals, etc; Electronic books